(untitled) (Derna Academy Journal for Applied Sciences, 2025)
Co-amoxiclav (CA), which is effectively used in the treatment of several number of bacterial infections, may cause nephrotoxicity. Cinnamon extract contains natural products which showed antioxidant, anti-inflammatory and anti-bacterial properties. In the present study, two doses of CA, therapeutic (30 mg/kg) and double therapeutic (60 mg/kg), were orally given to rats alone or in combination with cinnamon (200 mg/kg) for 10 consecutive days, to test the potential protective impact of cinnamon extract against CA-induced nephrotoxicity. Obtained results showed significant increases in serum concentration of creatinine (Cr), urea (Ur) and uric acid (UA) in rats treated with CA. Renal contents of malondialdehyde (MDA), protein carbonyl (PC), hydrogen peroxide (H2O2) and nitric oxide (NO) were also markedly increased following administration of CA. On contrary, treatment with CA produced significant decreases in the renal levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GRd), glutathione-s-transferase (GST) and reduced glutathione (GSH). The drug was also found to induce up regulation of pro-apoptotic p53 and caspase-3 proteins expression, while it down regulated the expression of the anti-apoptotic protein Bcl-2 in the kidney of treated rats. CA-induced adverse effects in all investigated biochemical indices seemed to be dose-dependent. However, administration of cinnamon extract along with CA to rats reduced renal injury, oxidative stress and apoptosis caused by treatment with CA alone. It could be concluded that cinnamon extract may be useful in the protection against CA-induced renal damage in rats